INTEGRATING AUTHENTIC MILITARY TEXTS TO DEVELOP READING COMPREHENSION SKILLS IN MILITARY EDUCATION - Javahir Aghayeva (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
Reading comprehension is a critical skill in military education, where learners are required to process complex, context-specific information accurately and efficiently. This paper argues that integrating authentic military texts into language instruction significantly enhances reading comprehension by aligning learning materials with learners’ professional needs and real-world tasks. Drawing on theories of authentic materials, English for Specific Purposes, and reading comprehension development, the study examines how exposure to genuine military documents: such as field manuals, operational reports, and training directives-supports deeper textual understanding and learner engagement. From a student-researcher perspective, the paper critically analyzes existing literature and classroom practices to demonstrate that authentic texts promote vocabulary acquisition, strategic reading, and contextual inference more effectively than simplified or artificial materials. Furthermore, the paper contends that authentic military texts contribute to learner motivation and professional identity formation, as students perceive a direct connection between classroom learning and future operational responsibilities. While acknowledging challenges such as text complexity and instructor preparedness, the study emphasizes the pedagogical value of carefully scaffolded authentic materials. Ultimately, this research highlights the importance of purposeful text selection and instructional support in maximizing the benefits of authenticity, concluding that authentic military texts are a valuable and necessary resource for developing reading comprehension in military educational contexts.